2023
DOI: 10.1021/acsomega.3c00387
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities of Low Viscous Biofuel─A Prospective Review

Abstract: Under the roof of solid industrialization and accelerated intensification of multiple ranges of mobilization, a huge rise in precious fuel consumption and pollution was observed. Based on the recent hardships of fossil fuels, experts are undoubtedly eager in carrying out their research in renewable environment-friendly fuels. There have been many reviews of works considering the parameters and standards of biodiesel, which is only from various vegetable and seed oils. But very little review work was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Excess oxygen provides a more favorable environment for combustion, facilitating the quick initiation and propagation of the flame front and thereby reducing the ID. Taken together, the superior fuel properties of MEMSO biodiesel, including improved ignition quality at higher temperatures, the presence of additives, and the excess oxygen content in the fuel, contribute to the lowest ID 40 42 observed at all loads in Figure 31 .…”
Section: Resultsmentioning
confidence: 91%
“…Excess oxygen provides a more favorable environment for combustion, facilitating the quick initiation and propagation of the flame front and thereby reducing the ID. Taken together, the superior fuel properties of MEMSO biodiesel, including improved ignition quality at higher temperatures, the presence of additives, and the excess oxygen content in the fuel, contribute to the lowest ID 40 42 observed at all loads in Figure 31 .…”
Section: Resultsmentioning
confidence: 91%
“…This could be rectified by the presence of the O 2 molecules in the combustion, which leads to improved combustion. Due to the high viscosity and low volatility of biodiesel, it affects the atomization properties of the fuel and leads to poor combustion. Further, the smoke opacities for the emulsified blends of B20CuO25, B20CuO50, B20CuO75, and B20CuO100 were found to be 11.6, 10.9, 10.1, and 10.3 N, respectively. B20CuO75 was revealed to have 17.58% lower smoke emissions than B20 without nanoadditive and 9.82% lower emissions than diesel.…”
Section: Resultsmentioning
confidence: 99%
“…In 2023, Ramalingam et al found that LE and PY are the most effective antioxidants for improving the oxidation stability of biodiesel. Compared to diesel, B20 produces the least amount of pollutants overall, except for NO x , whose emissions have been significantly reduced by the addition of LE 131 …”
Section: Biodieselmentioning
confidence: 99%
“…Compared to diesel, B20 produces the least amount of pollutants overall, except for NO x , whose emissions have been significantly reduced by the addition of LE 131 . 400 …”
Section: Biodieselmentioning
confidence: 99%